SILVER NANOPARTICLES EMBEDDED PAM/CMG HYDROGEL – IN-SITU GENERATION BY GREEN SYNTHESIS AND ITS ANTIMICROBIAL ACTIVITY - SUDHIR G. WARKAR,; A. P. GUPTA, (International Journal of Pharma and Bio Sciences, 2016)
Synthesis of silver nanoparticles using green chemistry process has become the prime focus of interest. This research article reports the in-situ generation of silver nanoparticles during copolymerization of polyacrylamide/carboxymethyl jargon crosslinked hydrogel through green route that is without using toxic reducing agents and solvents. The formation of silver nanoparticles was characterized by Ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, Energy dispersive analysis of X-ray, transmission electron microscopy and X-ray diffraction methods. All these methods confirmed the formation of Ag NPs during hydrogel synthesis. The silver nanoparticles produced in polyacrylamide/carboxymethyl guargum hydrogel matrix were also examined for antimicrobial activity against E.Coli.